The Effect of Concentration of Sugar and pH on the Quality of Nata de Yammy from Yam Starch Waste Liquid - Eka Wardhana; Herla Rusmarilin; Era Yusraini (Universitas Sumatera Utara, 2016)
This research was conducted to determine the effect of sugar concentration and pH on the quality of nata de yammy from yam starch waste liquid. This research was conducted using completely randomized design (CRD) with two factors: concentration of sugar (G) : (5% ; 7,5% ; 10%) and pH (P) : (4,0; 4,1; 4,2; 4,3; 4,4; 4,5). The parameters analyzed were pH after fermentation, water content, ash content, total acid after boiling, total sugar, total soluble solid, total plate count, nitrogen content, fiber content, the score value of color, the hedonic value of color, the hedonic value of flavour, the score value of taste, the hedonic value of taste and the score value of texture and the hedonic value of texture. The results showed that the concentration of sugar had highly significant effect on water content, ash content, total acid after boiling, total soluble solid, nitrogen content, total sugar, crude fiber content, the score value of color, the score value of taste, the hedonic value of taste and the score value of texture and the hedonic value of texture. pH had highly significant effect on pH after fermentation, water content, total acid after boiling, nitrogen content, the score value of color and the score value of texture. The interaction between the two factors had highly significant effect on the score value of texture and had significant effect on water content. Concentration of sugar of 5% and pH of 4,2 produced the best quality of nata from yam starch waste liquid. Keywords : nata, pH, sugar concentration, yam starch waste liquid.